Can early thinning and pruning lessen the impact of pine plantations on beetle and ant diversity in the Patagonian steppe? - Corley, Juan Carlos; Villacide, Jose Maria; Vesterinen, M. (2018)
Pine plantations are thought to negatively impact species diversity and to irreversibly modify arid zones. However, some studies have suggested that through the application of appropriate management practices, the negative impacts of plantations may be reduced. Our aim was to study the effects of early pruning and thinning on the ground-dwelling insects found in pine tree plantations in Patagonia. We compared the abundance, species richness and composition of the beetle and ant assemblages within 16-year-old pine stands (n = 10) subjected to early pruning and thinning (i.e. before canopy closure) against a steppe habitat exposed to sheep grazing (‘control’, n = 10). To sample ground-dwelling insects, we deployed nine pitfall traps per plot (100 m2) for a 10-day period. Vegetation cover and plant species richness were significantly lower in the plantations than in the steppe. We found that beetle species richness was reduced in the managed plantations in comparison to the steppe but abundance was higher. In turn, species composition in the plantations was different from that of the controls. Ant species richness was similar among habitats but abundance was lower in the plantations. We conclude that, contrary to our expectations, management practices that lead to sparse plantations at early stages in the production cycle, do not offer a significant advantage in terms of reducing the impact of pines on ground-dwelling insects of Patagonia.